39‐2: Development of Advanced LTPS TFT Technology for Low Power Consumption and Narrow Border LCDs. Issue 1 (29th May 2019) - Watakabe, Hajime; Jinnai, Toshihide; Suzumura, Isao; Hanada, Akihiro; Onodera, Ryo; Tada, Masahiro; Mochizuki, Kazuhide; Tanaka, Hitoshi; Ito, Tomoyuki
Abstract : We have developed an advanced LTPS TFT technology in which top‐gate oxide TFTs are used in each pixel and CMOS LTPS TFTs are used in gate drivers and multiplexers in the peripheral circuits. Oxide TFTs have excellent Ids –Vgs characteristics with a small Vth shift under negative bias temperature illumination stress (NBTIS).